Kształtowanie świadomości nauczycieli w dyskursie internetowym – media społecznościowe w nauczaniu języków obcych - Krajka, Jarosław; Maciaszczyk, Sylvia (Neofilolog, 2019)
The purpose of the present paper is to investigate the phenomenon of social media in language teaching. After a brief definition of social media, a general picture of conditions for Internet-based teaching and learning in Poland will be presented, based on the data collected by statistical offices and the present authors. The major part of the paper will be occupied by a summary of the most important findings from a qualitative study into the perceptions of social media by language learners in Poland, Latvia and Romania. The study, operated within the European research network Language Learning and Social Media – Six Key Dialogues (LS6 Network) and funded with the support of the European Commission, consisted of 60 interviews carried out with individuals of varying degrees of computer use and familiarity with Web 2.0 technologies.